Measurement of Trends in Wellbeing, Poverty, and Inequality with Case Studies from Bolivia and Colombia - Melanie Grosse (Peter Lang International Academic Publishers, 2011)
Reducing poverty and increasing wellbeing in developing countries have become central aims of both the national policy-makers as well as the international community. With the Millennium Development Declaration of 2000, the international community has agreed to focus on poverty reduction and the reduction of deprivation in its many dimensions. This book investigates conceptual and empirical issues on the measurement of trends in wellbeing, poverty, and inequality, illustrated for Bolivia and Colombia. The book contributes significantly to filling data gaps by combining existing data in a new way. Furthermore, it presents an important step forward to focus more on multidimensional outcomes of wellbeing rather than on monetary inputs and to develop tools to monitor the progress in achieving the Millennium Development Goals (MDGs).
Keywords: 330